Lutsk City space evolution under modernization conditions (end of the XIXth – beginning of the XXth century) - Bilyk, Viktoriia A. (Drohobych State Pedagogical University named after Ivan Franko, 2019)
The purpose of the article is to analyze Lutsk city space evolution at the turn of the XIXth and XXth centuries by analyzing the network of educational institutionsʼ development in the city and the city territory arrangement. The methodology of the research is based on the principles of historicism, scientificity, the authorʼs objectivity and the use of the general scientific (analysis, synthesis, generalization) and special-historical (historical-typological, historical-systemic) methods. The criticism and classification methods were applied at the archival materials processing stage. The scientific novelty is that for the first time on the basis of the archival materials Lutsk povit development has been illustrated, its territory expansion, the urbanization improvement and the urban population increase have been depicted at the turn of the century, which was the result of urbanization as a manifestation of modernization processes. These processes spheres of life has been determined. The Conclusions. One of the modernization manifestations of the second half of the XIXth century was the urbanization processes, which resulted in the increase in the number of cities and towns, territorially increasing existing urban settlements. The modernization also affected Lutsk povit, having a decisive influence on the development of its cultural, educational and territorial space. We have considered the evolution of the educational institutionsʼ network in the city, the cemeteries and squares organization, the urban improvements are some of the most striking examples of the urban space evolution, but not the last. There is a need for a comprehensive study of the city infrastructure development – the city streets construction and improvement, their electrification, the telephone communications emergence, the water supply and more. Due to the ethno-confessional diversity of the city, a separate and thorough study dedicated to the Lutsk City Society should be carried out. Therefore, both special and general works on Lutsk development history in terms of modernization conditions are not only possible but also necessary in the future.
Keywords: Lutsk; city space; modernization; urbanization; educational institutions; cemeteries; square; 94(477.82-25)«18/19»